Penerapan Model Picture and Picture untuk Meningkatkan Aktivitas dan Minat Belajar Siswa dalam pelajaran IPS Materi Jenis Pekerjaan - Munawaroh, Nadiyatul; Supriatna, Encep (Didaktika, 2022)
The underlying point of this research is that when done learning in the classroom is still oriented to the teacher (teacher centered learning), the teacher explains more material to students and after that gives tasks to be done so that thay do not talk much and roam in the classroom. This will make the child more passive when learning in the classroom. Limited knowledge that teachers have becomes a major factor, making it difficult for teachers to create interesting learning and invove student activities, therefore, this study wanats to review the use of picture and picture models during the IPS learning process to develop students’ learning activities and interests. The research design used during this study uses the KemmisMC. Taggart Class Action Research (CAR) method. This research takes place starting from the pre-action stage and the stage of implementation of action, namely cycle I and cycle II whice consists of 4 stages, namely the stage of planning, implementation, observation, and reflection. To obtain data in the study, researchers used observation techniques, interviews, tests and documentation. Data found based on the result of the percentage of student activity levels during cycle I which is 49,9% also during cycle II, there was an increase of 88,3% with the category of interest. So in this study researchers councluded that the uses of picture and picture learning models on IPS subjects found an increase in activity as well as the learning interests of grade IV students.